Participação do sistema histaminérgico neural na recuperação funcional de Meriones unguiculatus após lesão isquêmica unilateral encefálica - Garção, Diogo Costa (2013)
The aim of the first study was to investigate behavioural alterations and Fos expression in gerbils submitted to functional training after unilateral cerebral ischaemic injury. The behavioural procedures that were used to test functional recovery were the vibrissal stimulation test and the pellet-collecting task. Twenty-four hours after surgery, the animals were submitted to the experimental procedure, which lasted three weeks. The animals were distributed into four subgroups: sham lesion, sham lesion and trained, ischaemic injury and ischaemic injury and trained. The motor cortex, hippocampus and dorsal striatum were subjected to immunohistochemistry reaction for Fos expression, and the mean number of cells in each region was calculated. Behavioural data were analysed using the Kruskal Wallis test (p ≤ 0.05), and the morphological data were subjected to one-way Analysis of Variance, both followed by the Student-Newman-Keuls test (p ≤ 0.05). The animals in the injury group presented significantly lower averages in the pellet-collecting task and higher percentages of error in the vibrissal stimulation test when compared to animals in the sham lesion group, indicating that the lesion impaired motor performance in both tests. After training, the trained groups showed a significant increase in the pellet-collecting task compared to untrained groups, demonstrating that functional training improves task performance in sham and injured animals. A significant increase in the activation of neurons in the motor cortex and hippocampus of the injury and trained group was observed when compared to the injured group. Functional training increased the motor performance of the trained animals, independently of lesion, in the pellet-collecting task and caused increased neuronal activation in the motor cortex and hippocampus in the injury animals. Moreover, the presented method is useful for the evaluation of motor performance in gerbils. The objective of the second study was to investigate the effects of the histamine precursor L-Histidine and the H1-receptor antagonist Pyrilamine on the functional recovery of gerbils (Meriones unguiculatus) following a unilateral ischemic brain injury. Two experiments were conducted under the same experimental procedures to test the effects of two pharmacological treatments in experiment I, L-Histidine doses of 100 mg/kg and 200 mg/kg and in experiment II, Pyrilamine was administered at doses of 35 mg/kg and 70 mg/kg. Both experiments were accompanied by control groups for the drug (saline), the lesion (sham lesion) and training on the pelletcollecting task (untrained). The behavioural tests that were used to test functional recovery were the vibrissal stimulation test and the pellet-collecting task. The Kruskal-Wallis test (p<0.05), the Student-Newman-Keuls multiple comparison test (p<0.05) and a Bonferroni correction (p<0.025) were used for statistical analysis. It was established that a unilateral cerebral ischemic injury impairs motor performance and that training on the pellet-collecting task improves performance independently of the lesion. L-Histidine impaired functional recovery when administered in combination with motor training, while Pyrilamine in combination with training potentiated functional recovery. With respect to the vibrissal stimulation test, the injured animals that received training in combination with L-Histidine showed a memory recall deficit; however, Pyrilamine had the opposite effect in animals that were injured and trained. These results suggest that the neural histaminergic system participates in the process of functional recovery of gerbils following a unilateral ischemic brain injury.